Preparation and Characterization of Lead Oxide Nanoparticles by Laser Ablation as Antibacterial Agent - Baghdad Science Journal (مجلة بغداد للعلوم)
In this work, lead oxide nanoparticles were prepared by laser ablation of lead target immersed in deionized water by using pulsed Nd:YAG laser with laser energy 400 mJ/pulse and different laser pulses. The chemical bonding of lead oxide nps was investigated by Fourier Transform Infrared (FTIR); surface morphology and optical properties were investigated by Scanning Electron Microscope (SEM) and UV-Visible spectroscopy respectively, and the size effect of lead oxide nanoparticles was studied on its antibacterial action against two types of bacteria Gram-negitive (Escherichia coli) and Gram-positive (Staphylococcusaurus) by diffusion method. The antibacterial property results show that the antibacterial activity of the Lead oxide NPs was inversely proportional to the size of the nanoparticles in both Gram-negative and Gram-positive, and also it has been found that Gram-positive bacteria possess have greater sensitivity and less resistance to the lead oxide nanoparticles compared with Gram-negative bacteria.